Silicon Isotopes Reveal a Non-glacial Source of Silicon to Crescent Stream, McMurdo Dry Valleys, Antarctica - Hirst, Catherine; Opfergelt, Sophie; Gaspard, François; Hendry, Katharine R.; Hatton, Jade E.; Welch, Susan; McKnight, Diane M.; Berry Lyons, W. (Frontiers in Earth Science, 2020)
In high latitude environments, silicon is supplied to river waters by both glacial and non-glacial chemical weathering. The signal of these two end-members is often obscured by biological uptake and/or groundwater input in the river catchment. McMurdo Dry Valleys streams in Antarctica have no deep groundwater input, no connectivity between streams and no surface vegetation cover, and thus provide a simplified system for us to constrain the supply of dissolved silicon (DSi) to rivers from chemical weathering in a glacial environment. Here we report dissolved Si concentrations, germanium/silicon ratios (Ge/Si) and silicon isotope compositions (δ30SiDSi) in Crescent Stream, McMurdo Dry Valleys for samples collected between December and February in the 2014-2015, 2015-2016 and 2016-2017 austral seasons. The δ30SiDSi compositions and DSi concentrations are higher than values reported in wet-based glacial meltwaters, and form a narrow cluster within the range of values reported for permafrost dominated Arctic Rivers. High δ30SiDSi compositions, ranging from + 0.90 ‰ to + 1.39 ‰, are attributed to (i) the precipitation of amorphous silica during freezing of waters in isolated pockets of the hyporheic zone in the winter and the release of Si from unfrozen pockets during meltwater-hyporheic zone exchange in the austral summer, and (ii) additional Si isotope fractionation via long-term Si uptake in clay minerals and seasonal Si uptake into diatoms superimposed on this winter-derived isotope signal. There is no relationship between δ30SiDSi compositions and DSi concentrations with seasonal and daily discharge, showing that stream waters contain DSi that is in equilibrium with the formation of secondary Si minerals in the hyporheic zone. We show that δ30SiDSi compositions can be used as tracers of silicate weathering in the hyporheic zone and possible tracers of freeze-thaw conditions in the hyporheic zone. This is important in the context of the ongoing warming in McMurdo Dry Valleys and the supply of more meltwaters to the hyporheic zone of McMurdo Dry Valley streams.